Clinical outcomes of a new aspheric monofocal intraocular lens - Baha Toygar; Özge Yabaş Kızıloğlu; Okan Toygar; Ali Murat Hacımustafaoğlu (Beyoglu Eye Journal, 2018)
INTRODUCTION[|]To evaluate the clinical outcomes of a new aberration-free aspheric monofocal intraocular lens (IOL).[¤]METHODS[|]This single-center retrospective study included eyes of cataract patients implanted with a new aberration-free aspheric IOL. Medical records of patients who were followed for 6 months were reviewed. Data on visual acuity (distance, intermediate and near), refractive error (sphere, cylinder and manifest spherical equivalent [MSE]), contrast sensitivity and adverse events were collected and analyzed.[¤]RESULTS[|]Thirty-eight eyes of 30 patients with a mean age of 65.7+-10.6 years were included in the study. At 6 months postoperative, 100% of the eyes had achieved a corrected distance visual acuity of 0.2 logMAR or better, 89% of the eyes had achieved a corrected intermediate visual acuity of 0.2 logMAR or better and 89% of the eyes had achieved a corrected near visual acuity of J3 or better. Postoperatively, there was a significant reduction in the spherical (p<0.01) and cylindrical (p=0.01) refraction compared to baseline with a mean final MSE of 0.03+-0.40 diopters. Postoperative low contrast (10%) visual acuity remained stable (p= 0.54) through follow-up visits with a mean of 0.35+-0.17 logMAR at the 6-month visit. There were no adverse events associated with the study IOL. [¤]DISCUSSION AND CONCLUSION[|]The study IOL was safely implanted without any adverse events and improved visual acuity in cataract surgery patients while preserving visual quality over the 6-month follow-up period. Further studies with larger study groups and long term follow-up are necessary to confirm these results. [¤]